Challenges of senior 8-year-program medical students' scientific research in China: A multicenter questionnaire-based study. Issue 10 (11th March 2022) - Wan, Mengyao; Liu, Shuang; Zhu, Jiawei; Xiao, Sulong; Yuan, Lei; Lei, Xiaokang; Lei, Hao; Shi, Xiaomin; You, Wen; Ruan, Gechong; Li, Ji
Abstract : Abstract: Among the diverse medical education systems in China, the 8-year program is dedicated to cultivating physician scientists. Although the research ability of senior students in 8-year medical programs is a pivotal quality, it remains unclear. This study aimed to clarify the current status and challenges of students' research experience, abilities, and outputs. A multicenter cross-sectional study was conducted in 5 medical schools in northern China. Electronic questionnaires were sent to 235 randomly chosen fifth-grade or sixth-grade 8-year-program medical students. A total of 211 responses were collected and analyzed using SPSS 22.0. Only 13.3% of participants chose research as their future career goal. Students generally felt that conducting research was stressful and difficult. The greatest obstacle was a lack of time due to heavy workloads. The 2 major motivations for research were graduation and/or future employment (75.8%) and research interest (24.2%). More than half of the students (142, 67.3%) had research experience by the time of the survey, among whom 84 students already had research outputs. A higher proportion of students with outputs was motivated by the requirements for graduation or employment compared to students without outputs (71.4% vs 55.2%, P   =   .046 ). Senior 8-year-program medical students in China generally had high pressure to conduct research and devoted their efforts to overcome these challenges. More guidance and novel encouragement to enhance students' initiative and interest in research could be provided by medical schools and educators in the future.